Brain functional changes across the different phases of bipolar disorder. (February 2015) - Pomarol-Clotet, Edith; Alonso-Lana, Silvia; Moro, Noemi; Sarró, Salvador; Bonnin, Mar C.; Goikolea, José M.; Fernández-Corcuera, Paloma; Amann, Benedikt L.; Romaguera, Anna; Vieta, Eduard; Blanch, Josep; McKenna, Peter J.; et al.
Abstract : Background: Little is known about how functional imaging changes in bipolar disorder relate to different phases of the illness. Aims: To compare cognitive task activation in participants with bipolar disorder examined in different phases of illness. Method: Participants with bipolar disorder in mania ( n = 38), depression ( n = 38) and euthymia ( n = 38), as well as healthy controls ( n = 38), underwent functional magnetic resonance imaging during performance of the n-back working memory task. Activations and de-activations were compared between the bipolar subgroups and the controls, and among the bipolar subgroups. All participants were also entered into a linear mixed-effects model. Results: Compared with the controls, the mania and depression subgroups, but not the euthymia subgroup, showed reduced activation in the dorsolateral prefrontal cortex, the parietal cortex and other areas. Compared with the euthymia subgroup, the mania and depression subgroups showed hypoactivation in the parietal cortex. All three bipolar subgroups showed failure of de-activation in the ventromedial frontal cortex. Linear mixed-effects modelling revealed a further cluster of reduced activation in the left dorsolateral prefrontal cortex in the patients; this was significantly more marked in the mania than in the euthymia subgroup. Conclusions: Bipolar disorder is characterised by mood state-dependent hypoactivation in the parietal cortex. Reduced dorsolateral prefrontal activation is a further feature of mania and depression, which may improve partially in euthymia. Failure of de-activation in the medial frontal cortex shows trait-like characteristics.